Expanding the field of audit and consulting services services in conditions of economic independence of business entities (Diversity Research: Journal of Analysis and Trends, 2023)
In the coming years, specialists of audit firms should carry out not only a set of works to adapt internationally recognized principles and standards of decentralized control to the conditions of the innovative economy, but also be guided by generally accepted auditing standards for control and consulting activities. It is also noted that audit firms must respond, and even then not to the full extent, but only to the extent necessary for the country to expand foreign economic, industrial, trade and economic relations. At the same time, independent specialists of audit firms established in our country, based on relevant research by domestic professionals in the field of accounting, auditing, control and analysis of economic activity, should be able to further significantly complement the international practice of auditing the final results of various business systems.